Search for neutrino generated air shower candidates with energy ≥ 1019 eV and Zenith angle θ - Knurenko Stanislav; Petrov Igor; Sabourov Artem (EPJ Web of Conferences, 2017)
The description of the methodology and results of searching for air showers generated by neutral particles such as high energy gamma quanta and astroneutrinos are presented. For this purpose, we conducted a comprehensive analysis of the data: the electron, the muon and the EAS Cerenkov light, and their response time in scintillation and Cherenkov detectors. Air showers with energy more than 5·1018 eV and zenith angle θ ≥ 55∘ are selected and analyzed. Search results indicate a lack of air shower events formed by gamma-rays or high-energy neutrinos, but it does not mean that such air showers do not exist in nature; for example, experiments that recorded showers having a marked low muon content, i.e., “Muonless”, are likely to be candidates for showers produced by neutral primary particles.